Challenges facing community home based caregivers of people living with HIV/AIDS: case of Hope Humana Care program in Mabvuku - Tayisepi, Evernice (Midlands State University, 2017)
The researcher sought to study on the Challenges facing Community Home Based Care Givers of people living with HIV/AIDS. The research was well furnished with a couple of theories, relevant literature by other authors and previous studies that supported the research. The participants were sampled using purposive sampling. The research comprised of Hope Humana staff, Hope Humana Voluntary Caregivers and the HIV/AIDS affected individuals who made up a total of thirty two respondents who had an unequal representation of males and females. Interviews and a focus group discussion which constituted questions that were meant to highlight the challenges facing caregivers of the HIV/AIDS infected people were used. Data was analysed using qualitative descriptive methods and was presented in the form of discussion. Major findings were that caregivers of the chronically ill have been neglected in so many ways by their parent Organisations and even the Government which as a result strains them as they cope with the caregiving stresses. The study also revealed that the most common sources of stress included lack of support, financial burdens, inadequate caregiving material to do the caregiving duties, workload and lack of counselling. Recommendations to the mother project were given in order to curb the challenges faced by the caregivers of people living with HIV/AIDS. The recommendations include frequent trainings and counselling, formation of support groups, provision of caregiving materials as well as incentives for motivation.